On a difference equation with min-max response - George L. Karakostas; Stevo Stevic (International Journal of Mathematics and Mathematical Sciences)
We investigate the global behavior of the (positive) solutions of the difference equation xn+1=αn+F(xn,…,xn−k), n=0,1,…, where (αn) is a sequence of positive reals and F is a min-max function in the sense introduced here. Our results extend several results obtained in the literature.